Alternatives for Sustained Disaster Risk Reduction: A Re-assessment - Le De, Loic; Baumann, Louise L; Moatty, Annabelle; Le Masson, Virginie; Kikano, Faten; Fayazi, Mahmood; Fernandez, Manuela; Tomassi, Isabella; Cadag, Jake Rom D (AOSIS, 2023)
Alternatives for sustained disaster risk reduction’ was published in 2010 by Francophone and Anglophone researchers as a critique on the way disasters were studied and disaster risk reduction handled in the Francophone sphere. The authors criticized the dominant Francophone approach for being heavily hazard-centred and called for more emphasis on vulnerability to understand disasters and foster disaster risk reduction – a shift that had already taken place in the Anglophone disaster literature. Twelve years later, this paper draws upon a bibliographic analysis to examine if the arguments developed in the 2010 publication have stem attention in the Francophone disaster literature.Contribution: The article finds that the shift towards the vulnerability paradigm has, to some extent, happened but took much longer in the French context than in the Spanish language and the Asian disaster literature. The article emphasises the need for a re-assessment of our practices and study of disasters, including reflections on what disasters are studied, how, by whom, and for whom. Eventually, alternatives for sustained disaster risk reduction now and in the future might include drawing upon more diverse ontologies and epistemologies that are pertinent locally, considering local people as co-researchers though participatory methods, and empowering local Francophone researchers to play a greater role in researching disasters and leading disaster risk reduction in their own localities.